Development of the Edpuzzle Platform as an Audio Visual Learning Media for Arabic Language Learning at Madrasah Aliyah - Rachman, Andy; Sutisna, Dede; Khalik, Muh Fihris; Nitin, Mahon; Sopiandi, Ii (Journal International of Lingua and Technology, 2024)
The development of technology is currently growing so rapidly, various applications and online media are becoming increasingly popular to be used as learning media, including Youtube and Edpuzzle which can be used as learning support platforms with interactive, effective and fun video media for students. Arabic language learning with audio visual is needed by madrasah Aliyah students, so that learning is not boring and more interesting. This research aims to develop the Edupuzzle platform as an audio-visual learning media for Arabic language learning in madrasah Aliyah. The method used in this research is research and development with the Kemp model. Kemp's model is a learning design model designed in the early part of education aims to provide guidance to learners to think about general problems and learning objectives. The results of this study explain that the Edpuzzle platform can be used as audio-visual learning media in learning Arabic with audio visuals that can facilitate students in learning Arabic online. The conclusion of this research is that the Edpudzzle platform can be used as a learning medium for teachers, especially in Arabic language learning. the limitation of this research is that researchers only conduct research on the Edpudzzle platform for Arabic language learning, for that researchers hope that future researchers can conduct research with the same platform but more explained to support the teaching and learning process in other subjects.